Novel autoimmune response in a tauopathy mouse model - Nogueras-Ortiz, Carlos J.; De Jesus-Cortes, Hector J.; Vaquer-Alicea, Jaime; Vega, Irving E. (Frontiers in Neuroscience, 2014)
Molecular diagnostic tools with non-invasive properties that allow detection of pathological events in Alzheimer’s disease (AD) and other neurodegenerative tauopathies are essential for the development of therapeutics. Several diagnostic strategies based on the identification of biomarkers have been proposed. However, its specificity among neurodegenerative disorders is disputable as the association with pathological events remains elusive. Recently, we showed that Amphiphysin-1 (AMPH1) protein’s abundance is reduced in the central nervous system (CNS) of the tauopathy mouse model JNPL3 and AD brains. AMPH1 is a synaptic protein that plays an important role in clathrin-mediated endocytosis and associates with BIN1, one of the most important risk loci for AD. Also, it has been associated with a rare neurological disease known as Stiff-Person Syndrome (SPS). Auto-antibodies against AMPH1 are used as diagnostic biomarkers for a paraneoplastic variant of SPS. Therefore, we set up to evaluate the presence and abundance of auto-AMPH1 antibodies in tau-mediated neurodegeneration. Immunoblots and enzyme-linked immunosorbent assays (ELISA) were conducted to detect the presence of auto-AMPH1 antibodies in sera from euthanized mice that developed neurodegeneration (JNPL3) and healthy control mice (NTg). Results showed increased levels of auto-AMPH1 antibodies in JNPL3 sera compared to NTg controls. The abundance of auto-AMPH1 antibodies correlated with motor impairment and AMPH1 protein level decrease in the CNS. The results suggest that auto-AMPH1 antibodies could serve as a biomarker for the progression of tau-mediated neurodegeneration in JNPL3 mice.